Habitat and diet of Bhutan takin Budorcas taxicolor whitei during summer in Jigme Dorji National Park, Bhutan. Issue 11 (26th March 2016) - Wangchuk, Tshewang R.; Wegge, Per; Sangay, Tiger
Abstract: Little is known about the ecology of the rare and vulnerable Bhutan takin Budorcas taxicolor whitei, a large and basically forest-dwelling goat-antelope inhabiting mountain valleys in northern Bhutan. In Tsharijathang valley (3800 m asl) in Jigme Dorji National Park, we described the summer habitat of this takin subspecies through vegetation transects and by studying diet via microhistological analysis of faeces supplemented by examination of feeding sites. The habitats utilized by the c .250 animals occupying the valley consisted of six main vegetation types with roughly equal coverages, viz. three forest types (dominated by Juniperus, Betula or Abies ), alpine scrub (mainly low Rhododendron shrubs), open alpine meadow (mainly graminoids and forbs) and semi-open willow shrub (mainly Salix and forbs). Sixty-eight food species were identified in the feeding sites, but the bulk of the diet consisted of ≈10 species, the same species that also dominated the faecal material. With >50% of the diet consisting of shrubs, mainly Salix myrtillacea, the takins were mainly browsers. When foraging, they exhibited a weak form of selection by choosing sites with a slightly higher coverage of the most important food species and, while at these, proportionally more feeding signs were recorded. Domestic yak Bos grunniens are allowed to graze in the study area during winter when the takins have descended to lower elevation. At the present grazing pressure, the wintering yaks probably benefit the takin by maintaining the open vegetation structure, but their numbers and impact on the habitat should be monitored to prevent adverse effects.